Analisis Metode Pembelajaran Baru: Project-Based Learning (PjBL) di Era Modern - Ririn widya saputeri; Jasiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Islamic Religious Education in the modern era faces significant changes because students live in a digital environment that requires active, contextual, creative learning rather than memorization-based instruction. However, studies on Project-Based Learning in Islamic Religious Education still mostly emphasize learning outcomes, while its relevance to modern Islamic education, digital literacy, and moral formation requires deeper analysis. The research problem is how Project-Based Learning is relevant to the needs of modern Islamic Religious Education, and the objective is to analyze the role of PjBL in developing active, meaningful, and applicable Islamic learning. The data were processed through library research by selecting, classifying, reducing, and analyzing Indonesian books and journal articles published between 2020 and 2025. The findings show that PjBL strengthens five main aspects: religious understanding, collaboration, creativity, Islamic digital literacy, and students’ social responsibility. Therefore, PjBL is relevant for modern Islamic Religious Education because it connects Islamic teachings with students’ real-life practices.